Making Global Health Rotations a Two-Way Street - Michael B. Pitt MD; Sophia P. Gladding PhD; Charles R. Majinge MD; Sabrina M. Butteris MD (SAGE Publishing, 2016)
As US residency programs are increasingly offering global health electives for their trainees, there is a growing call for these opportunities to include bidirectional exchanges-where residents from both the US and international partner institutions rotate at the other's site. Curricular, logistical, and funding challenges of hosting residents from an international site may be barriers to developing these programs. In this report, the authors describe an 8-year experience of a US institution hosting residents from a resource-limited international partner and provide a framework for others institutions to develop bidirectional exchanges. They also report the visiting international residents' perceptions of the impact of the exchange on their clinical practice, teaching, career paths, and their home institution.